Developing the Vocational Training Report of Vietnam : lessons learned for international TVET cooperation - Erckelens, Britta van [Verfasser]; Lassig, Philipp [Verfasser]; Viet, Nguyen Quang [Verfasser] (My University, 2014)
"The Vocational Training Report of Vietnam, the first of its kind in the ASEAN region, is a milestone in building the monitoring and reporting capacities needed for reforms in Technical and Vocational Education and Training (TVET). The article provides insights into how the Vietnamese National Institute for Vocational Training (NIVT) strengthened its capacities (competencies of personnel, procedures, resources) in order to develop the Vocational Training Report in the frame of a trilateral cooperation with the German Federal Institute for Vocational Education and Training (BIBB) and the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). It finally draws lessons learned from this process for similar undertakings in other countries." (Autorenreferat, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 2.3.4 Asien; Berufsbildungspolitik; Berufsbildungsbericht; Bildungsmonitoring; Internationale Zusammenarbeit; Bundesrepublik Deutschland; Vietnam